(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Acute Bacteriological diarrheal disease among children younger than 5 years old remains a major cause of morbidity and mortality worldwide. Severe infectious diarrhea in children occurs most frequently under circumstances of poor environmental sanitation and hygiene, inadequate water supplies, and poverty. In India, the control of diarrhoea disease (CDD), including promotion of breastfeeding, oral rehydration therapy and specific health education is a part of national strategies aiming to improve the quality of life and reduce the burdens caused by diseases. Despite this fact, diarrheal disease is still the second leading cause of infectious morbidity and mortality in children as well as in adults in India. The local epidemiology of diarrhea in most rural areas of Indian states has not been researched thoroughly. In addition, most studies in India have focused on a specific pathogen rather than identifying the most common pathogens of diarrhea among children in rural areas. Better understand the local epidemiology of diarrhoea disease could be a valuable contribution to the development of public health prevention. We therefore conducted a study in Indian Hospital in order to identify risk factors for diarrhea among children less than five years of age in this area.